Utilization of Virtual Reality Technology in Tourism Destination Promotion Strategy to Increase Tourist Attraction - Istiqlal, Istiqlal; Irsyad, Ziqrurrahman; Iswanto, Dedy (Aurora: Journal of Emerging Business Paradigms, 2024)
This study aims to explore the utilization of Virtual Reality (VR) technology in tourism destination promotion strategies to increase tourist attraction through a Systematic Literature Review (SLR) approach. The study was conducted by selecting literature from academic databases such as Google Scholar, Scopus, and DOAJ, using keywords such as “virtual reality,” “destination promotion,” and “tourism” within the time span of 2014-2024. The results showed that VR significantly influenced travelers' perceptions by creating deep emotional engagement and increasing visit intentions. VR is also able to strengthen destination image through immersive experiences that enrich tourists' interactions with virtual environments. However, challenges were found in the adoption of VR by certain demographic groups, such as elderly travelers who tend to be more resistant to this technology. This research highlights the gaps in understanding regarding the wider application of VR, as well as the need for further research to develop effective and holistic promotional strategies to integrate VR with conventional methods. Future research should focus on ways to maintain the authenticity of the tourist experience through VR as well as reaching more diverse market segments.